Prevalence and determinants of depression, anxiety, and stress among the elderly population in Bangladesh: A cross-sectional study - Sahabul Haque; Suchana Akter; Lamia Jannat; Zidan Ahmed; Mohammad Arifur Rahman; Imran Hossain Sumon; Md. Mahfuzur Rahman; Md. Salah Uddin; Md. Moyazzem Hossain (PLoS ONE, 2026)
Background Mental health issues are commonly faced by the elderly population aged 60 and above, who are influenced by various risk factors, i.e., financial, family, social, and others that impact their quality of life. This study intends to identify the prevalence of depression, anxiety, and stress among the elderly population of Bangladesh and their associated factors. Method This cross-sectional study collected primary data from a sample of 400 elderly individuals aged 60 and above across four districts in Bangladesh. Depression, anxiety, and stress levels were measured using the PHQ-9, GAD-7, and PSS-10 scales, respectively. The ordinal logistic regression model is fitted to evaluate the effects of socio-demographic factors, and a confirmatory factor analysis is used to identify risk factors via a structural equation model. Result Findings revealed that 5.3% of elderly people have severe depression, 9.3% severe anxiety, and 4.75% high perceived stress. Older adults with poor health status were more likely to suffer from severe depression and anxiety. Social isolation and loneliness influence depression in old age. Significant risk factors include poor medical support from family and inadequate family relationships as age progresses, social discrimination and prejudice, and perceived social status. These factors were significantly associated with mental health problems (depression, anxiety, and stress) among the elderly population aged 60 and above. Conclusion Depression, anxiety, and stress are significant mental health issues among older people in Bangladesh. To ensure their quality of life, it is essential to diagnose and address these mental health problems to establish effective policies.